Lugares à venda: a construção de um processo visual a partir das marcas-território - Henriques, Fernanda (2010)
The object of this research was territory brands - a drawing and a slogan symbolically representing a place for the external market, namely in the tourism area -, focused on the Brazil Brand developed by Embratur in 2005 and on the Spain Brand developed by Turespaña in 1984. Here we question whether the brand representation is able to summarize different elements, such as dance, folklore, nature, climate, religion, language and all the remaining physical/economic/cultural regional characteristics, even if as a mosaic and heterogeneously, in one single image. The objective is to analyze how the complex codes of the Brazilian culture and Spanish culture were translated into brands' drawings supported by their communicational elements, such as colors, shapes, fonts and slogan. To understand the function of a commercial brand inside a consumer society we adopted as methodological base authors who discuss image and commercial brand, such as Adrian Frutiger, E. H. Gombrich, Joan Costa, Justo Villafañe and Rudolf Arnheim. In order to analyze how a symbol is received, added, transformed and developed by and for a culture we consulted authors who discuss semiotics and culture, such as Amálio Pinheiro, Edgar Morin, Jesús Martín-Barbero and Iuri Lótman. The methodology consisted of a bibliographical research and assessment of brand images, and the theoretical scenario includes the culture's semiotics, communication and cultural crossbreeding. In these four years of research, including a six-month period of sandwich-doctorate held in Seville, Spain, a significant increase could be seen in the number of territory brands launched by Latin American countries and in the world. As hypothesis under analysis we propose that creating territory brands arises from the need of building advertising symbols more flexible than national flags and coats of arms